KENDALI TEGANGAN TURBIN ANGIN SUMBU VERTIKAL DENGAN DC-DC BOOST KONVERTER - Khairunnisa Khairunnisa; Jazuli Fadil; Edi Yohanes; Syaiful Rachman; Muhammad Khalil; Antonius Rajagukguk (POLITALA PRESS, 2022)
All renewable energy, and all the potential that is currently being explored to face the challenges of global warming by researchers around the world. One of them is a wind turbine. This paper discusses the control of a standalone vertical axis wind turbine with PID controller. The development of turbine technology has been widely developed in terms of aerodynamics, generators, and power electronics configurations. we will explain about the control of a standalone type turbine with a simple control using PID controller. The wind turbine rotor is connected to a Permanent Magnet Synchronous Generator (PMSG), and DC-DC converter. PID controller is used to control the duty cycle of the converter mosfet, so that it can maintain the voltage when the wind speed continues to fluctuate. The simulation shows that PID is able to maintain a voltage with an overshoot value of 4.2%, and reaches a steady state of 0.2 s.